Catalogue of oribatid mites (Acari: Oribatida) from South Tyrol (Prov. Bolzano, Italy) - Schatz, Heinrich (Zootaxa, 2018)
A checklist of the oribatid mites reported in South Tyrol (Italy) is presented, covering all published records until 2017. Numerous unpublished records are added. Several species were revised, doubtful and erroneous records from previous publications are discussed and corrected if necessary. A total of 397 described species in 71 families are listed, complemented by two subspecies and 15 undetermined or undescribed species. The list includes all records of each species in South Tyrol, their known distribution in the Italian Alps sorted to provinces, the distribution in Italy, occurrence in the neighbouring countries Austria and Switzerland, and their general distribution. Occasional additional remarks give taxonomic information. A historical overview of the exploration of the oribatid mites in South Tyrol is outlined. The general distribution of the oribatid mite fauna of South Tyrol is analysed. Beside species with a wide distribution the region includes many “Mediterranean” species, species with their main distribution in Central Europe, and species restricted to the Alps, the latter mainly in higher mountainous regions.